2002
DOI: 10.1186/1475-2840-1-4
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in factors influencing insulin resistance in elderly hyperlipemic non-diabetic subjects

Abstract: Background: The increase in the prevalence of insulin resistance-related metabolic syndrome, a disorder that greatly increases the risk of diabetes, heart attack and stroke, is alarming. One of the most frequent and early symptoms of metabolic syndrome is hypertriglyceridemia. We examined the gender differences between various metabolic factors related to insulin resistance in elderly non-diabetic men and postmenopausal women of comparable age suffering from hypertriglyceridemia, and compared them with healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…Fasting blood glucose (FBG) and insulin were adequate according to the reference limits, but glycosylated haemoglobin (HbA1c) was higher than recommended (<5.7) in both sexes and could be indicative of predisposition to prediabetes, although the QUICKI values were comparable to those reported by Katz et al [ 23 ] in obese subjects. HOMA-IR values were similar to those of healthy volunteers in other studies [ 29 , 30 ]. Regarding glucose metabolism, there were no significant differences between sexes in any of the measured parameters, as shown in Table 4 .…”
Section: Resultssupporting
confidence: 87%
“…Fasting blood glucose (FBG) and insulin were adequate according to the reference limits, but glycosylated haemoglobin (HbA1c) was higher than recommended (<5.7) in both sexes and could be indicative of predisposition to prediabetes, although the QUICKI values were comparable to those reported by Katz et al [ 23 ] in obese subjects. HOMA-IR values were similar to those of healthy volunteers in other studies [ 29 , 30 ]. Regarding glucose metabolism, there were no significant differences between sexes in any of the measured parameters, as shown in Table 4 .…”
Section: Resultssupporting
confidence: 87%
“…Importantly, amelioration of glomerular hyperfiltration in type 2 diabetes has been shown to be associated with both improved insulin sensitivity (IS) and a slower decline in renal function over time5. Gender differences have been reported in factors affecting insulin resistance as well as renal function and progression to chronic kidney disease11121314. Sex hormones, body composition, and fat distribution are possible underlying mechanisms1214.…”
mentioning
confidence: 99%
“…Hattori et al found that in males, the relationship between serum leptin levels and the insulin resistance was not affected by the extent of glucose intolerance [ 27 ]. Lichnovská et al reported that in men the significance of correlations between serum leptin and insulin resistance was high and approximately the same in both the control and hyperlipemic groups, because the values of insulin resistance as well as serum leptin have nearly doubled in hyperlipemic in relation to control groups [ 28 ].…”
Section: Discussionmentioning
confidence: 99%